UZBEKISTAN BRONZE AGE AND IRON AGE CULTURAL AND ECONOMIC FORMATION OF MICRO OASES (Proceedings of International Educators Conference, 2024)
The article describes the history of the emergence of cultural and economic micro-oases of the Bronze Age and Iron Age of Uzbekistan.